2011
DOI: 10.1111/j.1755-3768.2010.01968.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of TGF‐β and FGF‐2 on in vitro proliferation and migration of primate retinal endothelial and Müller cells

Abstract: . Purpose:  During retinal development, the pattern of blood vessel formation depends upon the combined effects of proliferation and migration of endothelial cells, astrocytes and Müller cells. In this study, we investigated the potential for transforming growth factor‐β (TGF‐β) and fibroblast growth factor (FGF‐2) to influence this process by regulating proliferation and migration of retinal endothelial and macroglial cells. Methods:  We assessed the effects of exogenous TGF‐β and FGF‐2 on the proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…TGF-β was reported to enhance migration in both transformed and normal cells, including osteoblastic cells [1018]. However, there are reports that TGF-β can also inhibit migration of normal and transformed cells, indicating complex and potentially tissue-specific influences of TGF-β on migration [1921]. Tang et al [18] documented that TGF-β released during bone resorption is a chemotactic agent that recruits mesenchymal cells to the sites of resorption to begin the replacement phase of bone turnover.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β was reported to enhance migration in both transformed and normal cells, including osteoblastic cells [1018]. However, there are reports that TGF-β can also inhibit migration of normal and transformed cells, indicating complex and potentially tissue-specific influences of TGF-β on migration [1921]. Tang et al [18] documented that TGF-β released during bone resorption is a chemotactic agent that recruits mesenchymal cells to the sites of resorption to begin the replacement phase of bone turnover.…”
Section: Introductionmentioning
confidence: 99%
“…In the retina, MGCs play key structural and functional roles, and under physiological conditions these cells have a limited capability to migrate and proliferate. Nevertheless, in determined pathological abnormalities, MGCs can undergo functional and phenotypic changes, thereby acquiring the ability to migrate toward injured sites to promote retinal remodeling and cellular repopulation (41, 47). Although the regulatory mechanisms that promote this MGC migration are unclear, it has been proposed that ECM remodeling, produced by MMP‐2 and MMP‐9, may facilitate and induce the cellular migration of MGCs (22, 48).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, LRP1 reduction in MIO-M1 cells did not interfere with the cellular migration induced by the fibroblast growth factor 2 (FGF-2; ref. 41). Thus, we conclude that ␣ 2 M*-promoted MIO-M1 cell migration is mediated by LRP1.…”
Section: ␣ 2 M* Induces Mio-m1 Cell Migration Through Lrp1mentioning
confidence: 99%
“…In the retina, under certain pathologic abnormalities, MGC can undergo functional and phenotypic changes, thereby acquiring the ability to migrate toward injured sites to promote retinal remodeling and cellular repopulation. 73,74 In addition, it has been demonstrated that the humanderived MGC line, termed MIO-M1, exhibits stem cell properties and may be used for neuronal regeneration within mammalian retina. 38,75 Although these transplanted cells showed an acceptable integration, survival, and neural differentiation in animal retinas with neurodegenerative damage, the success of cellular therapy was relatively poor due to the absence of migratory properties.…”
Section: Discussionmentioning
confidence: 99%